(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Giving students the opportunity to be creative, through activities such as revising a story or changing its ending, can be a lot of fun, especially with students who have vivid imaginations. At the same time, the change in the routine from writing assignments individually to writing as a group can be very motivating for students who dislike writing in the first place. Furthermore, collaborative writing can be achieved using relatively simple techniques like the activity described in this article.